Analisis Kinerja Jalan dan Persepsi Pengguna terhadap Aksesibilitas Transportasi Berkelanjutan di Kawasan Wisata Toronipa - Makmur, Muzammil; Lakawa, Irwan; Ahsan, Laode Muhammad Fahrizal; Makmur, Muammar (Sultra Civil Engineering Journal (SCiEJ), 2025)
Improving accessibility to tourist areas is one of the key priorities in supporting the development of sustainable tourism. This study aims to evaluate the road performance leading to the Toronipa Beach tourist area in Kendari City and to assess user perceptions of its accessibility quality. The research employs a quantitative approach through technical analysis based on the Indonesian Highway Capacity Guidelines (PKJI) 2023 and user perception analysis using the Customer Satisfaction Index (CSI) method. Data were collected through traffic volume surveys and questionnaires distributed to 100 road users on weekdays and weekends. The analysis results indicate that the Level of Service (LOS) falls under category C on weekdays with a degree of saturation (DS) of 0.63, and category D on weekends with a DS of 0.81. The CSI analysis shows a satisfaction score of 74.2%, which is classified as “satisfied.” The dominant factors influencing user satisfaction include road physical condition, driving comfort, travel time, and the availability of supporting facilities. This study concludes that the improvement of road infrastructure between Kendari and Toronipa has significantly enhanced transportation performance and fostered positive user perceptions of accessibility to this coastal tourist destination